2002
DOI: 10.1002/rmv.339
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of HIV‐1 reverse transcription initiation

Abstract: During reverse transcription, the positive-strand HIV-1 RNA genome is converted into a double-stranded DNA copy which can be permanently integrated into the host cell genome. Recent analyses show that HIV-1 reverse transcription is a highly regulated process. The initiation reaction can be distinguished from a subsequent elongation reaction carried out by a reverse transcription complex composed of (at least) heterodimeric reverse transcriptase, cellular tRNA(lys3) and HIV-1 genomic RNA sequences. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 150 publications
0
15
0
5
Order By: Relevance
“…This region includes the PBS hairpin, displaying the PBS motif, which does not constitute a hot spot for genetic variation (21). Within this region, several interactions are required for efficient binding of the tRNA to the PBS in order to initiate reverse transcription, which is a critical step for viral replication (2,3,17). First, a cellular tRNA 3 Lys , which is used as a primer, binds the PBS motif in the 5Ј end of the viral RNA (4).…”
Section: Discussionmentioning
confidence: 99%
“…This region includes the PBS hairpin, displaying the PBS motif, which does not constitute a hot spot for genetic variation (21). Within this region, several interactions are required for efficient binding of the tRNA to the PBS in order to initiate reverse transcription, which is a critical step for viral replication (2,3,17). First, a cellular tRNA 3 Lys , which is used as a primer, binds the PBS motif in the 5Ј end of the viral RNA (4).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the selection of tRNA 3 Lys by HIV-1 for use as the primer in replication is unknown. Previous studies have suggested that the viral proteins nucleocapsid and reverse transcriptase or the Gag-Pol protein are involved in selection (3,8,18,19). Recent studies have demonstrated that the lysyl-tRNA synthetase is present in HIV-1 virions and may act as a chaperone for tRNA (4).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of recombinant RT with either the W401L or W401A mutation also demonstrated a complete inhibition of RNA-dependent DNA polymerase activity using the same synthetic template/primer used for our RT assays (51) and also using a template/primer based on the HIV-1 sequence (53). Therefore, one explanation for the difference in RT activity in infected cells compared to that in vitro may be due to the stabilizing presence of other viral or host cell factors that modulate RT activity in the reverse transcription complex (17,19,54,55,63). Another possibility for the difference in RT activity of W401 mutants in cell-free assays compared to intracellular reverse transcription can be ascribed to the dimerization constant of the RT.…”
Section: Discussionmentioning
confidence: 99%